PSIKOLOGIS PENGARANG DALAM LIRIK LAGU ALBUM “DOSA, KOTA, DAN KENANGAN” KARYA SILAMPUKAU - Malendra Pradana, Tio; Pramujiono, Agung (Buana Bastra, 2019)
This research is motivated by the fact that each of the creative process in the creation of aliterary work is a personal reflection author. The personal things, including psychologicalfactors within the author closely related to the events that the author never experienced in thepast. In addition to the author's personal experience, culture and literacy authors also take partin determining the quality of a literary work. In this study, the researchers raised concernsabout the psychology of the author of the lyrics of the song Silampukau. The purpose of thisstudy was to describe how the association psychology author of the lyrics of the song album"Dosa, Kota, dan Kenangan" by Silampukau have correlation with this author. The approachused in this study is expressive approach, whereas the type of research is descriptive. The dataused in this study is a written record. Data is written in the form of song lyrics tenSilampukau, among others Balada Harian, Si Pelanggan, Puan Kelana, Bola Raya, Bianglala,Lagu Rantau, DOA 1, Malam Jatuh di Surabaya, Sang Juragan, and Aku Duduk Menanti.Sources of data in this study is the physical release / CD album "Dosa, Kota, dan Kenangan"by Silampukau which contains ten songs. In this study, the techniques used to collect data isthe technique see and record. Researchers in this study do penyimakan careful to use languagethat is used by Silampukau analyzed in every song on the album "Dosa, Kota, dan Kenangan"by Silampukau to get the lyrics or the words used in the songs. Based on the results of dataanalysis found that there are some songs that have a link between the psychology of theauthor with his work. On Balada Harian, is a reflection of sadness and anger against theauthor and his work routine. At Puan Kelana’s song author also tells about his affair with aformer girlfriend through the expression and comparison between Paris and Surabaya. In thesong DOA 1 also contained an expression of sadness, grief, and anger poet on his way inbecoming a musician as well as a critique of the music industry in Indonesia today.